Isolasi dan Identifikasi Mikoriza Asal Tanah Gambut di Bawah Tegakan Kelapa Sawit (Elaeis guineensis Jacq.) di Beberapa Kabupaten di Riau (Jurnal Agro Teknologi Tropika, 2014)
Isolation and utilization of peat soil mycorrhizae have been started, yet for local peat soils of Riau has not beenwidely studied. The odjective of this study were to determine the types of mycorrhizae on oil palm plant stands on peatland in several districts in Riau. Peat soil sampling in several Bengkalis districts (Bantan Middle Village, DistrictBantan), Kampar (Village Rimbo Panjang, District Tambang), Pelalawan (Sungai Ara Village, District Sungai Ara) andSiak (Temusai Village, District Bunga Raya). The research was conducted in the laboratory with soil sampling inaccordance with the purposes of research and analysis in the laboratory according to the method of each parameter.This study had found that 2 genus Acaulospora spores and Glomus. The genus consists of Acaulospora, Acaulosporatuberculata, Acaulospora foveata and Glomus genus consists of Glomus diaphanum, Glomus etunicatum and Glomussp.1. but the types of spores are more dominant in the 4th District is the kind of spores Glomus sp.1.Keywords : isolation, identification, peatsoil, mycorrhizae, palm oil